Towards person-centred maternal and newborn care in Ethiopia: a mixed method study of satisfaction and experiences of care - Tigist Eshetu; Eshcolewyine Fekadu; Ahmed Abdella; Adiyam Mulushoa; Girmay Medhin; Merga Belina; Atalay Alem; Roxanne Keynejad; Tanya Robbins; Nadine Seward; Andrew Shennan; Louise M. Howard; et al. (BMC Pregnancy and Childbirth)
Abstract Background Person-centred maternal care is associated with positive experiences in high-income countries. Little is known about the transferability of this concept to non-Western, low-income settings. We aimed to explore women’s experiences of care and investigate satisfaction with antenatal care (ANC) in relation to person-centred care and unmet psychosocial needs in rural Ethiopia. Methods Design: facility-based, convergent mixed-method study. A cross-sectional survey included 2079 consecutive women attending ANC at eight health centres. Service satisfaction was measured using a 21-item validated measure. Independent variables: [1] person-centred care (1A: receipt of information; 1B: perceived adequacy of health worker responses) and [2] unmet psychosocial needs (2A: Patient Health Questionnaire for depressive symptoms; 2B: screening questionnaire for intimate partner violence (IPV)). Linear mixed effect regression assessed hypothesized associations between person-centred care/unmet psychosocial needs and service satisfaction, accounting for clustering at the health centre level. A linked qualitative study comprised eight in-depth interviews with women accessing ANC. Structured observations of ANC consultations rated health worker competencies (n = 65) and adherence to guidance promoting person-centred care (n = 53). Qualitative data were analysed thematically and triangulated with quantitative and observational data. Results Women reported lowest satisfaction in relation to family involvement (71.5% dissatisfied) and continuity of care (65.7% dissatisfied). As hypothesised, satisfaction increased with more information received (adjusted regression coefficient (ARC) 0.96 95%CI 0.71,1.20) but reported adequacy of help from health workers did not show a dose-response relationship (test-for-trend p = 0.157). Undetected depressive symptoms (ARC − 0.21 95%CI -0.27,-0.15) and IPV (ARC − 1.52; 95%CI -2.43,-0.61) were associated with lower service satisfaction scores. Most observed consultations scored low on most indicators of person-centred care. In qualitative interviews, women valued respectful and responsive communication from health workers, which affected their willingness to disclose psychosocial problems. Triangulation of findings indicated a mismatch between what women valued about care, their reported satisfaction with care and the actual care they were observed to receive. Conclusions Systems strengthening interventions to support person-centred maternal care appear contextually relevant but need to increase women’s expectations of care and agency to demand change. Prioritization of person-centred care could improve women’s experience of maternal care and better address psychosocial needs.